(untitled) (Academia Journal of Medicine, 2020)
Background: Anemia is one of the common Hematological disorders in India and worldwide. It affects all the age groups both in Males and Females. Moderate to Severe Anemia causes increased morbidity and mortality in elderly patients (AWHO expert group) - According to Worlds Health Organization, Anemia is a define when adults males are having Hemoglobin less than 13.5gr% when adults females non-pregnant less than 12 gr% and when pregnant females are having less than 11 ger%. The incidence of Anemia is very high in old age people who are more than 75 years of age. It ranges from 9% to 41%. In India Anemia is commonly due to nutrition, pregnancy, Hookworm infestation, DUB in the case of females, and Malignancy. The prevalence of anemia in the elderly has been found to range from 9% to 42% with the highest prevalence in 80 years and above. The common causes of anemia in India are Nutritional, Pregnancy, Hookworm infestation, and DUB in the case of Females and Malignancy. The common symptom is General weakness, Fatigue, Lack of concentration, Shortness of Breath, and Palpitations. A WHO expert group proposed that anemia should be considered when hemoglobin level below 13.5gr& in adult males; 12gr% in adults females non-pregnant; 11 gr% in adult female pregnant; 12gr% in children over 14yrs(1). The aim is to evaluate the etiology and clinical features of anemia in adults in rural medical colleges. Subjects & Methods: This study is conducted at GEMS Medical College, Srikakulam, A.P for the period of 1 year from April 2018 to March 2019. This study includes 120 patients with Anemia. The age group is between 20 years and 70 years. Males were 56 and females were 64. Results: We have conducted this study at GEMS Medical College, Srikakulam for 1 year, from April 2019 to March 2019 total no. of patients included in this study are 120 males 56 and females 64. The age group is between 20 years and 70 years. The maximum patients are in between 30 years and 70 years in both sexes. Conclusion: Anemia is a common medical problem in developing countries. In a rural part of India, the disorders will complicate the pregnancy also. So periodical examination and education of the people can decrease morbidity and mortality. In our area still, the common cause is nutritional.